Propozycja badań naukowych dla nauczyciela - Kabat, Małgorzata (Wydawnictwo Naukowe UAM w Poznaniu, 2003)
St. Żeromski’s words reflect the meaning of current knowledge that lays a certain way of thinking referring to reality and conducted research. The beginning of the 21st century, together with its informational technology, led teachers to adopt what St. Palka calls the attitude of a researcher who can construct the hypotheses or scientific facts resulting from practical or theoretical activity (or both). Facts can be confirmed or invalidated thanks to the following: diagnostic research, experimental or evaluative research, verification research, action research and others. Getting to know these types of research and obtaining certain pieces of information from them enables us to introduce modifications and improvements into the educational process. This entails certain specific tasks in teacher’s educational process. This article concerns the following problems: - the presentation o f image of today’s teacher and of the factors that are essential and that make the realization of professional development difficult, what follows is the discussion of selected research, - the process of professional training and improvement of teacher’s research skills, - the presentation o f proposals Donald Medley’s "triangular projects models” of the teacher’s effective work - an alternative that teachers can use in the acquiring of research competence.
Proposal for pedagogical research